Pharmacokinetic/pharmacodynamic integration of cefquinome against Pasteurella Multocida in a piglet tissue cage model. Issue 1 (8th November 2018) - Zhang, Longfei; Wu, Xun; Huang, Zilong; Kang, Zheng; Chen, Yuqin; Shen, Xiangguang; Cai, Qinren; Ding, Huanzhong
Abstract: To explore the in vivo antimicrobial activity of cefquinome against Pasteurella multocida in piglets, a piglet tissue cage infection model was used in this study. After the population of P. multocida reached 10 7  CFU/mL in a tissue cage, piglets received an intramuscular administration of cefquinome at 0.2, 0.4, 0.8, 1, 2, and 4 mg/kg once daily for 3 days. To assess the tissue cage pharmacokinetics (PKTCF) of cefquinome, tissue cage fluid was collected for cefquinome analysis at 1, 3, 6, 9, 12, and 24 hr after each of the 3 daily drug administrations. Bacteria were counted every 24 hr after drug administration and at 48 and 72 hr after the last administration. Evaluation of the relationship between pharmacokinetic/pharmacodynamic (PK/PD) parameters and the antibacterial effect showed that the surrogate of % T  > minimum inhibitory concentration (MIC) ( R 2  = 0.981) was the best PK/PD index that correlated with effectiveness of cefquinome against P. multocida . The respective values of % T  > MIC required for continuous 1/3‐log, 1/2‐log, and 1‐log reductions were 14.23, 34.45, and 73.44%, respectively, during each 24‐hr treatment period. In conclusion, cefquinome exhibited a potent antibacterial effect against P. multocida . When % T  > MIC reached 73.44%, cefquinome exhibited a bactericidal effect against P. multocida after three successive daily administrations.